2020
DOI: 10.1111/gbb.12649
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant mechanism of classical herbal formula lily bulb and Rehmannia decoction: insights from gene expression profile of medial prefrontal cortex of mice with stress‐induced depression‐like behavior

Abstract: According to traditional Chinese medicine, lily bulb and Rehmannia decoction (LBRD) is a specialized formula for the treatment of "lily disease", the symptoms of which resemble the clinical manifestations of major depression. However, the molecular basis of the antidepressant mechanism of LBRD and the quality marker ingredients of LBRD remain unclear. This study aimed to investigate the quality marker ingredients of LBRD and to show the molecular mechanism of its antidepressant activities. In this study, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Therefore, the chronic exposure to excess cortisol eventually leads to insulin resistance and concomitant metabolic syndromes including type 2 diabetes as well as mental disorders including depression ( Rhyu et al, 2019 ). Furthermore, the decreased or insufficient secretion of monoamine transmitters in the brain, such as norepinephrine (NE), dopamine (DA), γ-aminobutyric (GABA), and serotonin (5-HT), is also a major cause of comorbid diabetic depression ( Hashim et al, 2016 ; Ma et al, 2019 ; Mukherjee and Chaturvedi, 2019 ; Zhang et al, 2020 ). Experimental studies have revealed that impairment of 5-HT causes nerve cell damage and decreases neurogenesis, leading to anxiety and depression ( Mahar et al, 2014 ; Yohn et al, 2017 ).…”
Section: Tcm and Natural Products With Effects On Changes In Nervous mentioning
confidence: 99%
“…Therefore, the chronic exposure to excess cortisol eventually leads to insulin resistance and concomitant metabolic syndromes including type 2 diabetes as well as mental disorders including depression ( Rhyu et al, 2019 ). Furthermore, the decreased or insufficient secretion of monoamine transmitters in the brain, such as norepinephrine (NE), dopamine (DA), γ-aminobutyric (GABA), and serotonin (5-HT), is also a major cause of comorbid diabetic depression ( Hashim et al, 2016 ; Ma et al, 2019 ; Mukherjee and Chaturvedi, 2019 ; Zhang et al, 2020 ). Experimental studies have revealed that impairment of 5-HT causes nerve cell damage and decreases neurogenesis, leading to anxiety and depression ( Mahar et al, 2014 ; Yohn et al, 2017 ).…”
Section: Tcm and Natural Products With Effects On Changes In Nervous mentioning
confidence: 99%
“…Studies on the binding of mTOR with different proteins to form functional polymer complexes suggested that BDNF/mTOR1 can be used as a research focus for a new generation of antidepressant drugs [ 178 ]. The BDNF/mTOR1 signaling pathway may be the target of the antidepressant effect of traditional prescriptions (lily bulb and Rehmannia decoction) [ 179 ].…”
Section: Role Of Brain-derived Neurotrophic Factor In Depressionmentioning
confidence: 99%
“…And the classical TCM formula, Liuwei Dihuang Pills , with the function of nourishing kidney yin, is the major formula for Xiao Ke disease of yin deficiency and internal heat ( Zheng et al, 2019 ). Moreover, Lily Bulb and Rehmannia Decoction has long been used as tonics for nourishing heart and lung, clearing heat and cooling blood in the treatment of mental instability, absent mindedness, dysphoria, and depression ( Chi et al, 2019 ; Zhang et al, 2019 ; Zhang et al, 2020 ). The above three examples are typical cases of TCM formulas for the treatment of hot syndrome.…”
Section: The Classification and Treatment Of Cold And Hot Syndromesmentioning
confidence: 99%